O significado do atendimento ao adolescente na atenção básica à saúde: uma análise compreensiva - Natalia de Cassia Horta (2007)
This qualitative study adopted a phenomenological approach and aimed to understand the meaning of health professionals care delivery to adolescents in the basic health network. The research was carried out at two health centers in Belo Horizonte/MG. Study participants were fifteen Family Health Team professionals, including nurses, physicians, nursing auxiliaries and community health agents. Data were collected through an open interview, guided by the following question: What does it mean, for you, to deliver care to adolescents? The subjects discourse was analyzed according to comprehensive ideographic analysis in line with Martins and Bicudo (1989). Categories were initially interpreted in the light of Alfred Schutz, the precursor of Social Phenomenology.The comprehensive analysis of participants testimonies converged to three large categories that indicate how adolescents receive care in the basic health network: 1- Care delivery to the adolescent: experienced contradictions. Shows what challenges are met and limitations in care delivery to adolescents; 2- Care delivery to the adolescent: being in the world with the other. Deals with the relation between the health professional and the adolescent; 3- Care delivery to the adolescent in basic care: picture of a practice. Emphasizes adolescents andhealth services and the need to organize the service with a view to care delivery to this public. When reflecting about the meaning of this care for the professionals, we could apprehend that it is permeated by challenges in terms of their professional training and limitations imposed by the adolescent phase itself, leading to a sometimes conflicting, sometimes pacific relation between professionals and adolescents. This research appoints possible roads for care delivery to adolescents in basic health care, mainly focusing on health promotion and disease prevention. Interdisciplinary and multiprofessional work with adolescents, based on a welcoming and humanistic proposal, represents the main challenge for health professionals.